Comparative study between ‘Limberg flap’ and ‘excision with secondary wound healing’ in the management of sacrococcygeal pilonidalsinus - Singh, Nirbhay; Khan, Rafat; Garg, Nitin (International Surgery Journal, 2025)
Background: We conducted this comparative study between ‘Limberg flap’ and ‘excision with secondary wound healing’ to have a more informative data as far as surgical outcome is concerned for patients of sacro-coccygeal pilonidal sinus. Methods: This study was conducted as prospective observational study on patients of sacrococcygeal pilonidal sinus admitted in the Department of General Surgery, People’s Hospital, who have been selected for operative intervention by either of two procedures during the study period of 18 months. Depending upon surgical procedure, patients were divided into two groups, group A- Limberg flap (study group) and group B- excision with secondary wound healing (control group). Results: Mean duration of surgery was significantly higher in cases managed using Limberg flap technique as compared to excision and secondary healing. Mean pain scores, wound infection, time to wound healing, duration of hospital stay and time to return to normal activity were significantly lower in cases managed using Limberg flap as compared to excision at all the follow up (p<0.05). Mean patient satisfaction was found to be significantly higher in cases following Limberg flap group (p<0.05). Conclusions: Rhomboid excision with Limberg’s flap technique is better technique as compared to open excision with secondary healing technique in terms of less post-operative pain, less complications, early recovery, early wound healing, short duration of hospital stay, early return to normal activity and higher patient satisfaction. The only disadvantage with Limberg flap technique is higher mean duration of surgery, attributed to additional time required for raising and suturing of flap following excision.